Investigation on microstructure and electrical properties of Bi doping Ca3Co4O9 nanoparticles synthesized by sol-gel process - M A, Mohammed; Sudin, Izman; Mohd Noor, Alias; Rajoo, Srithar; M B, Uday; H. Obayes, Noor; Firdaus Omar, Muhammad (International Journal of Engineering and Technology, 2018)
In this study, nanoparticles of Bi doped Ca3-xCo4O9 [Ca3-xBixCo4O9 where x=0, 0.2, 0.4 and 0.6] were prepared by sol gel combustion method. The phase structures and microstructures of Bi doped Ca3-xCo4O9 powders preparation were investigated. The microstructural observations of different Bi doped Ca3-xCo4O9 powders were evaluated using X-ray diffraction analysis (XRD) and Variable Pressure Scanning Electron Microscope (VPSEM). The bulk Ca3-xBixCo4O9 samples were fabricated using uniaxial cold pressing technique. Electrical resistivity of bulk Ca3-xBixCo4O9 samples with different doping was measured using four-probe method from 300 to 700Â°K. The electrical resistivity was found to decrease with increasing temperature for the bulk Ca3-xBixCo4O9 samples. The electrical properties of Ca3-xBixCo4O9 are non-monotonic functions of x.Â